2019
DOI: 10.1155/2019/9517140
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Hedonic Hunger and Health Interest on Habit and Sodium Intake Patterns in Food Consumption

Abstract: Many people are motivated to eat healthily but find it difficult to override established and less healthy habits. Habits, by their nature, are unconscious and cued by the environment, thus making them powerful determinants of behavior. This study examined how hedonic hunger and health interest are related to habit and whether sodium consumption is mediated by hedonic hunger, health interest, and habit. A total of 117 students of Universitas Brawijaya took part in the study. Data analysis were done using Partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Hedonic Hunger is now considered the new measure of appetite that can be defined as the desire to consume more appetising food items in the absence of physical hunger [ 14 , 15 ]. The power of food scale assessment showed that hedonic hunger was moderately present in 51.3% of the individuals along with 23.3% of individuals who showed severe signs of hedonic hunger and were thought to have stronger stimulus towards consumption of delicious foods rich in salt, sugar, and fat.…”
Section: Discussionmentioning
confidence: 99%
“…Hedonic Hunger is now considered the new measure of appetite that can be defined as the desire to consume more appetising food items in the absence of physical hunger [ 14 , 15 ]. The power of food scale assessment showed that hedonic hunger was moderately present in 51.3% of the individuals along with 23.3% of individuals who showed severe signs of hedonic hunger and were thought to have stronger stimulus towards consumption of delicious foods rich in salt, sugar, and fat.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, if someone sees a social media ad about a new gourmet burger at a fast-food restaurant and has a positive attitude towards that ad, they are more likely to decide to try that burger on their next restaurant visit. This behavior could become a pattern if the individual finds the experience satisfying [73]. Previous studies in marketing and consumer psychology have demonstrated that attitudes towards advertising can influence purchasing decisions and, by extension, consumption patterns [9,36,49,70,76].…”
Section: Relationships Between Attitudes Towards Social Media Adverti...mentioning
confidence: 99%
“…Understanding it could be crucial to discern how consumer preferences and behaviors translate into specific food choices, or dietary habits, particularly in the context of fast food. Santoso et al [73], in their work on sodium intake, outline how consumption patterns are defined by repetitive behavior in a given situation. While the development of habits and patterns in daily routines (like eating) optimizes decisions, they might not always lead to positive outcomes if the products consumed are not healthy [5,21,[23][24][25][26].…”
Section: Relationships Between Attitudes Towards Social Media Adverti...mentioning
confidence: 99%
See 2 more Smart Citations